DOKTRIN TEOSOFI WAHDAT AL-WUJUD - Amin, Sagir M. (Hunafa: Jurnal Studia Islamika, 2005)
The God is a hidden essence. Thus, we need a special effort to understand His existence. Various efforts sufi of teaching made to know and even to unite with God have developed in Islam. One of them is Wahdat al-Wujud that tries to apprehend Godâs existence through tasawuf falsafi (philosophical mysticism). No one can deny that this sufi concept has brought about many criticisms since it has been considered deviating from tauhid (oneness) concept. However, it has been a part of Islamic knowledge treasury that persistently needs a deep inquiry.This article tries to discuss the intended concept to elucidate the core of itâs teaching.Kata Kunci: Wahdat al-Wujud, Mahiyah, Sufisme, Ibn Arabi